Farm Power Availability Pattern and Its Impact on Food grain Productivity in Madhya Pradesh - De, Dipankar; Chandra, Hukum; Singh, R S (Journal of Agricultural Engineering, 2002)
Farm mechanization in Madhya Pradesh grew slowly and accelerated recently due to increased need of timely completion of field operations, better utilization of costly inputs, need to handle large volume of agro-produce and improved quality of work. The unit farm power availability in the state has increased from 0.199 kW/ha in 1971-72 to 0.636 kW/ ha in 1998-99 at the rate of 4.40 per cent, and is likely to reach to 0.95 kW/ha by the year 2005. In the process, dependence on animal power has decreased from 66.23 per cent in 1971-72 to estimated 15.03 per cent by 2005. The unit power availability in the State had been 68.62 per cent of the national average in 1971-72 and is likely to be 63.33 per cent by the year 2005. The food grains production in the State was 8.58 million tonnes in 1956-57 and reached to 21.8 million tonnes in 1998-99 at annual growth rate of 2.25 per cent. The yield is however very low (1079 kg/ha) compared to all India average yield (1620 kg/ha). The unit power-productivity relationship for the State indicates that with increase in unit power availability, the crop productivity had increased as in the case of national scenario. Reliance on animate power has been a major cause of lower yield response to farm power availability as compared to the national scenario. Availability of adequate and proper mix of farm power is thus a critical input determining the quality and pace of mechanization of agriculture. In this paper an attempt has been made to examine the trend of farm power availability till the year 2005 and effects of its various sources in the State of Madhya Pradesh as compared to the national scenario. The trend of growth of tractive and total farm power availability has been examined in light of the growth in land productivity in order to provide an insight to the trend of mechanization in the State.